LEVELS OF NOISE EMITTED BY AGRICULTURAL TRACTORS - Baesso, M. M.; Modolo, A. J.; Baesso, R. C. E.; Fischer, C. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The exposure of workers to noise produced by agricultural tractors, which can be harmful to your health. This study aims to evaluate the levels of noise emitted by agricultural tractors of different powers and to compare the results with existing regulations in Brazil. This work, studied 22 tractors, was performed at the farms in Pirassununga, SP and Faculty of Animal Sciences and Food Engineering (FZEA) at the University of São Paulo in Pirassununga County, in an area owned by the Prefecture of the Campus USP Fernando Costa. To measure noise, Icel DL 4020 decibelimeter were used. The decibelimeter scale used were decibels dB (A), with the instrument adjusted to measure the machine noise with quick answer. Noise level above the maximum allowed for the work day of 8 hours was observed in all tractors studied.